Assessment of pancreatic duct damage following trauma: is endoscopic retrograde cholangiopancreatography the gold standard?. Issue 832 (February 1995) - Doctor, N.; Dooley, J. S.; Davidson, B. R.
Abstract : A 12-year-old girl was admitted as an emergency with blunt pancreatic trauma. Computed tomography (CT) showed an intact pancreas. She failed conservative treatment. Endoscopic retrograde cholangiopancreatography (ERCP) demonstrated division of the pancreatic duct at the neck of pancreas. At laparotomy, however, there was complete necrosis of the pancreatic head. She recovered well following enteric drainage of the body of pancreas. CT and ERCP are considered the optimal imaging for pancreatic trauma but the findings may be misleading.